Attention Paid to Privacy Policy Statements - Tomáš Sigmund (Information, 2021)
The article deals with the topic of attention paid to online privacy policy statements by university students. Privacy policy statements were originally intended to mitigate the users’ privacy con-cerns and support trust, but users disregard them. The article uses the theory of planned behav-iour combined with privacy calculus to find and verify determinants of reading privacy policy statements. We used the survey method and evaluated the results with partial least square struc-tural equation modelling. We concluded that the attitude towards reading privacy policy state-ments is influenced by privacy risks and privacy benefits. The intention to read privacy policy statements is influenced by social norms, understanding the privacy policy and mainly by the willingness to spend time and effort reading the statements. The effect of attitude was also signif-icant, but its size was smaller. Finally, wider conclusions are drawn, as the confusion around pri-vacy policy statements is a symptom of a wider social change in the information society.